Ekoteologi Islam Sebagai Paradigma Transformatif: Rekonstruksi Epistemologi Sains Lingkungan, Akselerasi Teknologi Hijau Menuju Peradaban Berkelanjutan - Murjiah; Ani Cahyadi (Universitas Garut, 2026)
This article critically examines Islamic ecotheology as a transformative paradigm for reconstructing the epistemology of environmental science and accelerating the adoption of green technology. The twenty-first century ecological crisis—marked by anthropogenic climate change, mass biodiversity extinction, and systemic ecosystem degradation—cannot be reduced to mere technical failures; rather, it is rooted in an epistemological and spiritual crisis emanating from a materialistic-secular worldview. Islam, as a holistic theological system, proffers an ecotheological paradigm anchored in four ontological pillars: tawhid (divine oneness reflected in the unity of creation), khalifah (mandate of creaturely stewardship), amanah (divinely entrusted ecological responsibility), and mizan (cosmic balance that must be preserved). Employing an integrative-interconnective methodology with critical analysis of classical Islamic normative texts, the epistemology of historical Islamic science, and contemporary scientific literature on ecology and green technology, this study finds that: (1) Islamic ecotheology provides a more robust moral-spiritual foundation than secular environmentalism by anchoring ecological ethics in the transcendent; (2) the Islamic scientific tradition historically demonstrates an integrative model of scientific inquiry and ethical accountability relevant to contemporary ecological crises; (3) green technology is not merely compatible with but normatively mandated by the maqasid al-shari'ah; and (4) Islamic Religious Education requires a paradigmatic reorientation to incorporate the ecotheological dimension as an integral component of rahmatan muslim character formation. This article contributes to the development of Islamic ecotheology as an autonomous academic discipline with implications for educational and environmental policy in Indonesia